A modified formula using energy system contributions to calculate pure maximal rate of lactate accumulation during a maximal sprint cycling test - Yang, Woo-Hwi; Park, So-Young; Kim, Taenam; Jeon, Hyung-Jin; Heine, Oliver; Gehlert, Sebastian (Frontiers in Physiology, 2023)
Purpose: This study aimed to compare previous calculating formulas of maximal lactate accumulated rate (vLa.max) and a modified formula of pure vLa.max (PvLa.max) during a 15-s all-out sprint cycling test (ASCT) and to analyze their relationships. Methods: Thirty male national-level track cyclists participated in this study (n =30). They performed a 15-s ASCT. Anaerobic power output (Wpeak and Wmean), oxygen uptake, and blood lactate concentrations (La−) were measured. These parameters were used for different calculations of vLa.max and three energy contributions (phosphagen; WPCr, glycolytic; WGly, and oxidative; WOxi). PvLa.max calculation considered delta La−, time until Wpeak (tPCr−peak), and contributed time of the oxidative system (tOxi). Other vLa.max levels without tOxi were calculated using decreased time by 3.5% from Wpeak (tPCr −3.5%) and tPCr−peak. Results: Absolute and relative WPCr showed higher values compared to WGly and WOxi. Absolute and relative WGly were significantly higher than WOxi (p < 0.0001, respectively). vLa.max (tPCr −3.5%) was significantly higher than PvLa.max and vLa.max (tPCr−peak) while vLa.max (tPCr−peak) was lower than PvLa.max (p < 0.0001, respectively). A very strong correlation between PvLa.max and vLa.max (tPCr−peak) was found (r = 0.99, R2 = 0.98). It was higher than the relationship between PvLa.max and vLa.max (tPCr −3.5%) (r = 0.87, R2 = 0.77). vLa.max (tPCr−peak), PvLa.max, and vLa.max (tPCr −3.5%) correlated with absolute Wmean and WGly. Conclusions: PvLa.max as a modified calculation of vLa.max provides more detailed insights into inter-individual differences in energy and glycolytic metabolism than vLa.max (tPCr−peak) and vLa.max (tPCr −3.5%). Because WOxi and WPCr can differ remarkably between athletes, implementing those values in PvLa.max can establish more optimized individual profiling for elite track cyclists.